CPOT: A suitable tool for crack propagation path optimization based on image recognition. (January 2020) - Jiang, Kerong; Wang, Hu; Zhu, Lielang; Cheng, Cong
Highlights: A crack path optimization method is developed to control crack propagation along specified path. Image recognition technique is applied to extraction of crack propagation path. Several popular optimization algorithms are used to treat single crack and multiple cracks in 2-D and 3-D problems. A friendly graphical user interface is designed for users. Abstract: A Crack Path Optimization Tool (CPOT) is developed in this study, and it is designed as a plugin for ABAQUS/CAE. The CPOT provides a friendly graphical user interface, which can control crack propagation along the specified path effectively. With the arrangement strategy of holes, the tool can deflect the crack propagation path and avoid the critical domains or structures. In this application, optimization algorithm assisted extended finite element method ( XFEM) is applied to crack propagation analysis. Meanwhile, the image recognition technique is employed to extract the related crack coordinates from crack path image. The grayscale processing and binarization methods are used to obtain the pixels of crack path in the image processing module. Then, a conversion coefficient is proposed to convert the pixel coordinate into physical coordinate. Compared with the single crack optimization strategy, a recognition method for multiple cracks is added to distinguish different cracks path. Additionally, three-dimensional optimization problem is also considered in the application. Finally, several examples which utilize the deformation plasticity theory for the ductile crack problem are employed to illustrate the superiority of the application. The results indicate the high accuracy and efficiency of the application for controlling arbitrary crack propagation along the specified path.